Irving, Marshall County - Allen, Kyle (Kansas State University, The Chapman Center for Rural Studies, 2010)
Irving citizens were victim to many challenges, but for 100 years, they remained resilient and showed great grit in times of tragedy. The town was founded by stalwart, educated leaders who knew how to endure. Irving had all the potential to survive but faced too many diverse challenges. Ironically it was the federal government that led to the destruction of the town. Today, a stone marker points to the old town site, as do many such markers along the Blue River. They are granite signposts of a time when thriving river towns and their busy mills hummed in the valley.
Kyle Allen, “Irving, Marshall County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/22.
Keywords: Bleeding Kansas; General Samuel Wardens Mill; Irving; Marshall County; Samuel C. Pomeroy; Kyle Allen